Efeito da hCG ou deslorelina sobre a hemodinâmica folicular e perfil endogeno de LH em éguas cíclicas - Boakari, Yatta Linhares [UNESP] (2014)
Ovulation induction after treatment with hCG and GnRH analogs, such as deslorelin, occur through distinct mechanism. Meanwhile, it is possible that these treatments entail changes in follicular vascular perfusion during the pre-ovulatory period. Thus, color Doppler ultrasound presents a potential to be used as a tool for real-time assessment of follicles ovulatory potential in mares. The main purposes of this paper were to evaluate follicular vascular perfusion (FVP) after the use of ovulation induction hormones and the relationship with the plasmatic profile of LH. Additionally, evaluate if FVP can be used to indicate proximity to ovulation. Estrous cycles of mares were randomly divided in three experimental groups: GnRH group, hCG group and control group (n=10 mares/group). Treatments were done in the presence of a follicle with ≥35mm diameter associated with uterine edema. The moment immediately before treatment was considered H0. Blood collection and Doppler ultrasound exam with power-flow mode of the dominant follicle were done to evaluate, respectively, plasmatic concentration of LH and FVP. Parameters were evaluated every hour between H0-H12 and every six hours from H12 until H30. Additionally, GnRH and hCG groups were evaluated every hour from H30 until ovulation detection or until H48. In the control group, B-mode ultrasonography was completed every six hours after H30 and when detection of characteristics indicative of imminent ovulation Doppler ultrasonography was done every hour until ovulation detection. Control group presented a longer interval until ovulation (P < 0,0001). Group effect (P < 0.05) was detected for FVP. Animals from the GnRH group presented higher mean FVP (P < 0.05) when compared to the hCG and control groups since H0 until the moment of ovulation. No moment effect and interaction group:moment was found between experimental groups. Mean LH concentration between H1 and ...